2022
DOI: 10.7150/ijbs.71287
|View full text |Cite
|
Sign up to set email alerts
|

Lithocholic acid inhibits dendritic cell activation by reducing intracellular glutathione via TGR5 signaling

Abstract: Dendritic cells (DCs) are the major antigen-presenting cells and play an important role in autoimmune uveitis. Emerging evidence suggests that bile acids (BAs) regulate DCs maturation. However, the underlying mechanisms by which BAs regulate the function of DCs still need to be clarified. Here, we demonstrate that lithocholic acid (LCA) inhibits the production of pro-inflammatory cytokines and the expression of surface molecules in bone marrow-derived dendritic cells (BMDCs). LCA attenuates the severity of EAU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…During the development and progression of PCa, NF-κB/p65 is constitutively activated, and the mechanism involves an increased phosphorylation of inhibitor of NF-κB (IκB) protein (27,28). In this study, we found GPBAR1 inhibited the phosphorylation of IkBα, which promoted p65 phosphorylation release in vivo and in vitro (29). We previously showed that PA induced PCa cell apoptosis by inhibiting NF-κB activity (18).…”
mentioning
confidence: 59%
“…During the development and progression of PCa, NF-κB/p65 is constitutively activated, and the mechanism involves an increased phosphorylation of inhibitor of NF-κB (IκB) protein (27,28). In this study, we found GPBAR1 inhibited the phosphorylation of IkBα, which promoted p65 phosphorylation release in vivo and in vitro (29). We previously showed that PA induced PCa cell apoptosis by inhibiting NF-κB activity (18).…”
mentioning
confidence: 59%
“…28 Moreover, TGR5 agonists, that is, LCA and INT-777 treatment, increased the TGR5 expression in monocyte-derived DCs of patients with Behcet's disease. 29…”
Section: In Immune Cellsmentioning
confidence: 99%
“…63 Also, TGR5 activation inhibited glutathione production and induced oxidative stress, which led to apoptosis and autophagy in DCs. 29 As a result, TGR5 activation increases the production of FoxP3 + regulatory T cells and reduces the production of effector T cells. 54 For instance, TGR5 activation of tumourassociated macrophages mediated CD8 + T-cell suppression, while TGR5 activation of macrophages co-cultured with CD4 + T cells inhibited Th1 and Th17 polarization, as well as the release of IFN-γ and IL-17 in the culture supernatant.…”
Section: Tgr5 Activation Inhibits the Adaptive Immune Responsementioning
confidence: 99%
“…TGR5 and FXR are expressed in a variety of immune cells as two major receptors for BA. TGR5 has anti-inflammatory effects and reduces the production of inflammatory cytokines in monocytes, macrophages, and dendritic cells ( Hu et al, 2022 ). Activated TGR5 inhibits NLRP3 inflammasome activation via the TGR5-cAMP-PKA axis, thereby attenuating high-fat diet-induced elevated glucose tolerance, IR, and inflammatory responses ( Hu et al, 2021 ).…”
Section: Bile Acids and Type 2 Diabetes Mellitusmentioning
confidence: 99%